2010
DOI: 10.1002/9780470559277.ch090203
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Analogues as Probes for DNA and RNA Polymerases

Abstract: Nucleotide analogues represent a major class of anti‐cancer and anti‐viral drugs, and provide an extremely powerful tool for dissecting the mechanisms of DNA and RNA polymerases. While the basic assays themselves are relatively straightforward, a key issue is to appropriately design the studies to answer the mechanistic question of interest. This unit addresses the major issues involved in designing these studies, and some of the potential difficulties that arise in interpreting the data. Examples are given fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“… 39 In addition to 5-medCTP, previous studies also demonstrated that many other modified NTPs can be incorporated into DNA and RNA during in vitro replication and transcription. 14 , 16 , 40 42 In this respect, these detectable endogenous modified NTPs can be theoretically incorporated into DNA and RNA, which may compromise the regulatory roles of modifications.…”
Section: Resultsmentioning
confidence: 99%
“… 39 In addition to 5-medCTP, previous studies also demonstrated that many other modified NTPs can be incorporated into DNA and RNA during in vitro replication and transcription. 14 , 16 , 40 42 In this respect, these detectable endogenous modified NTPs can be theoretically incorporated into DNA and RNA, which may compromise the regulatory roles of modifications.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleoside or nucleotide analogue is an important class of antiviral therapeutics [83]. It is a powerful tool for dissecting the mechanisms and functions of viral DNA and RNA polymerases [84,85]. This screening selected top-ranking compounds with better binding scores than control compounds for further analysis.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Khasianine formed hydrogen bonding with a Gln997 side chain with a binding score of −7.1 kcal/mol (Figure 4C), while VER155008 was involved in making −8.7 Monensin [83]. It is a powerful tool for dissecting the mechanisms and functions of viral DNA and RNA polymerases [84,85]. This screening selected top-ranking compounds with better binding scores than control compounds for further analysis.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Cordycepin has been considered as a nucleoside analogue [ 4 ], which is able to be involved in the actions of DNA and/or RNA polymerases [ 17 ]. After entering into the cell, it becomes mono-, di-, and tri-phosphates of 3-deoxyadenosine [ 18 ].…”
Section: An Active Constituent Of Cordyceps Cmentioning
confidence: 99%